Th17 cells in alemtuzumab-treated patients: the effect of long-term maintenance immunosuppressive therapy. - Hester, J; Mills, N; Shankar, S; Carvalho-Gaspar, M; Friend, P; Wood, K (2011)
BACKGROUND: Leukocyte depletion at the time of transplantation with alemtuzumab (Campath-1H) has been demonstrated to be a potential strategy for reducing long-term exposure to immunosuppressive drugs. Although the impact of alemtuzumab treatment on the immune system has been explored, the effects of long-term immunosuppressive therapy in alemtuzumab-treated patients still need to be elucidated. METHODS: T-regulatory cells and Th1/Th17 responses were assessed by flow cytometry and real-time polymerase chain reaction more than 4 years after transplantation in 10 kidney recipients treated with alemtuzumab induction. Seven patients were converted to sirolimus monotherapy at 12 months posttransplant, whereas the remaining three patients with history of graft rejection were treated with sirolimus and mycophenolate mofetil. In addition, we sorted and expanded interleukin (IL)-17A-producing CCR6CD4 T cells and assessed their susceptibility to suppression by regulatory T (Treg) cells in in vitro suppression tests. RESULTS: Three years of mammalian target of rapamycin inhibitor monotherapy correlates with an increase in the number of IL-17A producing cells, compared with patients treated with sirolimus and mycophenolate mofetil. In these patients, IL-17A expression was compensated for by an increase in Treg cell frequency and number. In addition, we demonstrated that both proliferation and cytokine production by Th17 cells can be effectively regulated by Treg cells. CONCLUSIONS: Our results demonstrate that history of rejection and long-term maintenance immunosuppression has an impact on the number of circulating Treg and Th17 cells. However, more importantly, we have shown that Treg cells can effectively regulate Th17cells both in vitro and in vivo.